Why is history of historiography important? Problems of historians' identity in the Lithuanian historiography - Švedas, Aurimas; Gieda, Aurelijus (Lietuvos istorijos studijos, 2005)
This article discusses the limits of competence of the history of historiography. An attempt is made to answer the question, what positive effect could be gained from the investigations of the history of historiography for society, the historians' community, and individual researchers. Such a task could be posed considering the history of historiography as a complex discipline. Currently, efforts are made to evaluate the tradition of the research in the 20th century. The article raises an issue, whether it is possible to realize these efforts without conceptual history of historiography; hypotheses about alteration of identities of the community of Lithuanian historians are formulated.
Keywords: -